COP28 and its impact on the shared socioeconomic pathways - Patel, Ketan; Hansmeyer, Chris (Frontiers in Environmental Economics, 2024)
COP28 aimed to make essential progress on the climate transition following a year marked by unparalleled climatic extremities. A spectrum of extreme weather phenomena, including droughts, floods, and wildfires, inflicted considerable devastation across various global locales. 2023 was identified as the warmest on record, with mean global temperatures surpassing those of the pre-industrial era by 1.4°C by the WMO. Given the current trajectory of temperature escalation, it is projected that global temperatures will surpass the preindustrial baseline by 1.5°C circa 2026, significantly ahead of the target year 2100 established during the 21st Conference of the Parties (COP21) in Paris, 8 years prior according to UNEP. The progress made during COP28 will need to be operationalized along pathways that enable the commitments to be turned into outcomes.